SPE Annual Technical Conference and Exhibition 1981
DOI: 10.2118/10332-ms
|View full text |Cite
|
Sign up to set email alerts
|

Fracture and Vuggy Porosity

Abstract: The discovery of hydrocarbons in fractured rock always brings up the controversial subject of fracture porosity. Evidence of brecciation, leaching and infilling often complicate the issue. The high recovery efficiency of oil from fractures combined with the frequent absence of appreciable matrix porosity, in many cases enhance the economic importance of the estimated figures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Rotating and chipping of the enclosing block increased slightly, and applying the cubic control volumes increased the porosity values drastically. Still, these results were in accordance with other published data of caves with similar genesis (Weber and Bakker, 1981;Palmer, 1995;Heward et al, 2000), where the cave porosity can be 1-3%. The macro-scale conduit porosity results from the volumetric modeling were verified and confirmed by the modeling in the nearby Pál-völgy Quarry, where direct rock face measurements were carried out.…”
Section: The Pál-völgy Cave (Pvc)supporting
confidence: 93%
“…Rotating and chipping of the enclosing block increased slightly, and applying the cubic control volumes increased the porosity values drastically. Still, these results were in accordance with other published data of caves with similar genesis (Weber and Bakker, 1981;Palmer, 1995;Heward et al, 2000), where the cave porosity can be 1-3%. The macro-scale conduit porosity results from the volumetric modeling were verified and confirmed by the modeling in the nearby Pál-völgy Quarry, where direct rock face measurements were carried out.…”
Section: The Pál-völgy Cave (Pvc)supporting
confidence: 93%
“…Note also that matrix porosity measurements do not include fracture porosity, which becomes increasingly important at depth. A fracture porosity component of 1% has been added to the probable SS-GR resource calculations based on previous estimates of dual porosity at The Geysers geothermal field by Antúnez et al (1994), who stated "A 1% fracture porosity (secondary porosity) was assumed based on the work of Weber and Bakker (1981). Hulen et al (1991Hulen et al ( , 1992 reported fracture porosity values in the order of 1.5% based on porosity and permeability enhancements due to calcite dissolution."…”
Section: Porosity Estimatesmentioning
confidence: 99%
“…Published data on fractured carbonate reservoirs in strongly folded anticlines in Iran suggested a range of fracture porosity from 0.1-0.3%. These estimates were derived from material balance calculations (Weber and Bakker, 1981). Within Kurdistan published estimates of fracture porosity for various fi elds and discoveries are presented in Table 4.…”
Section: Oil-in-place Reserves and Recovery Effi Ciencymentioning
confidence: 99%